2002
DOI: 10.1128/jb.184.15.4246-4258.2002
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Expression of Periplasmic Proteins and Amino Acid Catabolism inEscherichia coli

Abstract: Escherichia coli grows over a wide range of pHs (pH 4.4 to 9.2), and its own metabolism shifts the external pH toward either extreme, depending on available nutrients and electron acceptors. Responses to pH values across the growth range were examined through two-dimensional electrophoresis (2-D gels) of the proteome and through lac gene fusions. Strain W3110 was grown to early log phase in complex broth buffered at pH 4.9, 6.0, 8.0, or 9.1. 2-D gel analysis revealed the pH dependence of 19 proteins not previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
305
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(322 citation statements)
references
References 68 publications
14
305
2
1
Order By: Relevance
“…Other short palindromic sequences were detected in the operon sequences, at positions corresponding to those described in the L. acidophilus and E. coli atp operons (36,44). In the ATPases complexes of these bacteria these palindromic sequences have been found to increase the mRNA stability and thus enhance the translational efficiency of the corresponding genes (21).…”
Section: Discussionmentioning
confidence: 90%
“…Other short palindromic sequences were detected in the operon sequences, at positions corresponding to those described in the L. acidophilus and E. coli atp operons (36,44). In the ATPases complexes of these bacteria these palindromic sequences have been found to increase the mRNA stability and thus enhance the translational efficiency of the corresponding genes (21).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, several proteins involved in molecular chaperoning (DnaK) (Slepenkov & Witt, 2002), acid tolerance response (YfiD) (Stancik et al, 2002), LPS core region biosynthesis (RfaE) (Valvano et al, 2000), transcriptional regulation and other functions were identified. Interestingly, YbeJ, a putative glutamate/aspartate periplasmic binding and transport protein (Tremoulet et al, 2002) was represented by one of the five unique spots from the wild-type.…”
Section: Proteins Regulated By Yjjqmentioning
confidence: 99%
“…pH also influences the culture conditions, including oxygenation, growth phase and metabolite composition. [16] Cell growth rate is also affected by pH, and low cell growth rate occurs at low pH. [17] Several enzymes related to the formation of acetate are induced at the pH extremes, including the proteins encoded by pta, sucB and sucC.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Several enzymes related to the formation of acetate are induced at the pH extremes, including the proteins encoded by pta, sucB and sucC. [16] Components of the tricarboxylic acid (TCA) cycle, such as sucB and sucC, are induced at low pH, which would be expected to result in utilization of the high proton potential and in increase of the TCA cycle capacity. [16,18] The key gene pta, which regulates pH, is involved in the synthesis of acetate and is induced at high pH that would be changed by the concentration of acetate.…”
Section: Introductionmentioning
confidence: 99%